Prognostic value of the HALP score in breast cancer: a systematic review and meta-analysis - Cai, Jia; Wang, Bo; Jing, Niancai; Zhang, Yue (Frontiers in Oncology, 2025)
BackgroundThe present research is a meta-analysis aimed at quantifying the influence of the hemoglobin, albumin, lymphocyte, and platelet (HALP) score on the overall survival (OS) and disease-free survival (DFS) in breast cancer patients. The objective of this research is to examine the prognostic significance of the HALP score in breast cancer patients and evaluate its predictive performance for survival outcomes.MethodsThis research was conducted adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We retrieved PubMed, EMBASE, Web of Science, Cochrane Library, and Google Scholar for studies relevant to the link between the HALP score and the prognosis of breast cancer up to July 3, 2025. The quality of the studies was appraised with Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) and the Newcastle-Ottawa Scale (NOS). MetaDiSc 1.4, Stata SE 18, and Review Manager 5.4 were leveraged to examine the risk of bias and to conduct statistical analysis.ResultsAmong 971 studies, nine fulfilled the inclusion criteria, encompassing a total of 4,560 individuals. An increased HALP score was linked to favorable OS (HR = 0.61, 95% CI 0.39-0.97, p < 0.05). No statistically significant association was noted between the HALP score and DFS in breast cancer patients. The area under the summary receiver operating characteristics (SROC) curve (AUC) of the HALP score for predicting pathological complete response (pCR) was 0.57.ConclusionElevated HALP scores may represent a prognostic biomarker for favorable survival outcomes in breast cancer patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero identifier CRD420251031999.